Dates, Places, Verses: Random Remarks on the Catalogue of the “Paṇḍit Collection” in the Royal Library, Copenhagen - Hinüber, Oskar von (Indo-Iranian journal, 2021)
Abstract Reviewing the catalogue of the Paṇḍit Collection in the Royal Library at Copenhagen, which was (as far as the colophons allow this conclusion) mainly collected from Western India and from Benares during the 16th through 19th centuries, offers also an opportunity for a preliminary study of some aspects of colophons, particularly the problems incurred in fully understanding the dates and their vocabulary. Moreover, concluding verses attached by copyists at the end of their manuscripts were assembled from the catalogue.